2009
DOI: 10.1021/jf803157j
|View full text |Cite
|
Sign up to set email alerts
|

Novel Key Aroma Components of Galbanum Oil

Abstract: Galbanum oil is composed of monoterpenes in large amounts and pyrazines in small amounts. Although the monoterpenes are the main components of galbanum oil, they hardly contribute to the distinct galbanum aroma. The scanty amounts of pyrazines, in contrast, contribute significantly to the aroma. Considering the complexity and potency of the odor, the essential oil was assumed to contain so far not identified compounds with high odor contribution. By the gas chromatography-mass spectrometry-olfactometry (GC-MS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The following compounds were purchased from commercial sources: hexanal, (Z)-hex-3-enal, 1,8-cineole, octanal, (Z)-hex-3-en-1-ol, nonanal, 2-isopropyl-3-methoxypyrazine, acetic acid, citronellal, decanal, (E)-non-2-enal, linalool, undecanal, (E)-dec-2-enal, dodecanal, (E)-undec-2-enal, citronellol, perillaldehyde, (2E,4E)-deca-2,4-dienal, geraniol, (E)-dodec-2-enal, eugenol, thymol, isothymol, indole, -pinene, myrcene, limonene, -terpinene, isoamyl alcohol, oct-1-en-3-one, (E)-hept-2-enal, (E)-oct-2-enal, benzaldehyde, (2E,6Z)-nona-2,6-dienal, 2-methylbutanoic acid, 2-acetyl-2-thiazoline, 2-phenylethanol, 4-hydroxy-2,5-dimethylfuran-3(2H)-one, methyl Nmethylanthranilate and vanillin (Sigma-Aldrich Japan, Tokyo, Japan); -damascenone (Firmenich, Meyrin, Switzerland); a mixture of 2-ethyl-4-hydroxy-5-methylfuran-3(2H)-one and 5-ethyl-4-hydroxy-2-methylfuran-3(2H)-one (Givaudan, Vernier, Switzerland); and tridec-1-ene (Tokyo Chemical Industry Co., Tokyo, Japan). The following compounds were synthesized by the methods reported in the literature: (3E,5Z)-undeca-1,3,5-triene, 26) (3E,5Z,8Z)-undeca-1,3,5,8-tetraene, 27) 6-methylheptanal, 28) 6-methyloctanal, 28) yuzunone ((6Z,8E)-undeca-6,8,10-trien-3-one), 29) yuzuol ((6Z,8E)-undeca-6,8,10-trien-4-ol), 30) (2E)-cis-4,5-epoxydec-2-enal, 31) (2E)-trans-4,5-epoxydec-2-enal, 32) (2E,7Z)-trans-4,5-epoxydeca-2,7-dienal 33) and wine lactone (3,6-dimethyl-3a,4,5,7a-tetrahydro-1-benzofuran-2(3H)-one). 34,35) All reagents and solvents were of analytical grade.…”
Section: Methodsmentioning
confidence: 99%
“…The following compounds were purchased from commercial sources: hexanal, (Z)-hex-3-enal, 1,8-cineole, octanal, (Z)-hex-3-en-1-ol, nonanal, 2-isopropyl-3-methoxypyrazine, acetic acid, citronellal, decanal, (E)-non-2-enal, linalool, undecanal, (E)-dec-2-enal, dodecanal, (E)-undec-2-enal, citronellol, perillaldehyde, (2E,4E)-deca-2,4-dienal, geraniol, (E)-dodec-2-enal, eugenol, thymol, isothymol, indole, -pinene, myrcene, limonene, -terpinene, isoamyl alcohol, oct-1-en-3-one, (E)-hept-2-enal, (E)-oct-2-enal, benzaldehyde, (2E,6Z)-nona-2,6-dienal, 2-methylbutanoic acid, 2-acetyl-2-thiazoline, 2-phenylethanol, 4-hydroxy-2,5-dimethylfuran-3(2H)-one, methyl Nmethylanthranilate and vanillin (Sigma-Aldrich Japan, Tokyo, Japan); -damascenone (Firmenich, Meyrin, Switzerland); a mixture of 2-ethyl-4-hydroxy-5-methylfuran-3(2H)-one and 5-ethyl-4-hydroxy-2-methylfuran-3(2H)-one (Givaudan, Vernier, Switzerland); and tridec-1-ene (Tokyo Chemical Industry Co., Tokyo, Japan). The following compounds were synthesized by the methods reported in the literature: (3E,5Z)-undeca-1,3,5-triene, 26) (3E,5Z,8Z)-undeca-1,3,5,8-tetraene, 27) 6-methylheptanal, 28) 6-methyloctanal, 28) yuzunone ((6Z,8E)-undeca-6,8,10-trien-3-one), 29) yuzuol ((6Z,8E)-undeca-6,8,10-trien-4-ol), 30) (2E)-cis-4,5-epoxydec-2-enal, 31) (2E)-trans-4,5-epoxydec-2-enal, 32) (2E,7Z)-trans-4,5-epoxydeca-2,7-dienal 33) and wine lactone (3,6-dimethyl-3a,4,5,7a-tetrahydro-1-benzofuran-2(3H)-one). 34,35) All reagents and solvents were of analytical grade.…”
Section: Methodsmentioning
confidence: 99%
“…[2] Song et al [3] first reported 46 odour-active compounds that were identified in cold-pressed yuzu peel oil using AEDA. Miyazawa et al [4] recently elucidated that (Z,E)-6,8,10-undecatrien-3-one and (Z,E)-6,8,10-undecatrien-4-ol, determined by AEDA, were new potent odorants contributing to the overall yuzu aroma on the basis of sensory evaluation. Recently, we analysed the volatile oil of yuzu using AEDA, with the result that the new odour-active aldehyde trans-4,5-epoxy-(E,Z)-2,7-decadienal was first identified as an aroma component.…”
Section: Introductionmentioning
confidence: 99%
“…The following compounds were synthesized as reported in the literature: (5 Z )‐1,5‐octadien‐3‐one, (3 E ,5 Z )‐1,3,5‐undecatriene, (6 Z ,8 E )‐6,8,10‐undecatrien‐3‐one and (2 E )‐ trans ‐4,5‐epoxy‐2‐decenal …”
Section: Methodsmentioning
confidence: 99%
“…The following compounds were synthesized as reported in the literature: (5Z)-1,5-octadien-3-one, [10] (3E,5Z)-1,3,5-undecatriene, [11] (6Z,8E)-6,8,10-undecatrien-3-one [12] and (2E)-trans-4,5-epoxy-2-decenal. [13] (3E,5E/Z,8Z)-1,3,5,8-Undecatetraene, 1…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation